Geopharmacosurveillance of reporting rates of events supposedly attributable to vaccination or immunization against COVID-19 - Thays Cristina Pereira Barbosa; Gabriela Lourença Martins do Nascimento; Luiz Henrique Arroyo; Ricardo Alexandre Arcêncio; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães (Revista Latino-Americana de Enfermagem)
Objective: to analyze the spatial distribution of the reporting rate of events supposedly attributable to vaccination or immunization against COVID-19 and factors associated with achieving the target recommended by the Global Vaccine Action Plan. Method: ecological study that considered notifications from 853 municipalities in the state of Minas Gerais. A total of 34,027 notifications recorded in the e-SUS Notifica system were analyzed. Getis-Ord Gi* and Geographically weighted regression were performed to identify spatial clusters, compliance with at least 10 notifications and factors correlated with spatial distribution. Results: a heterogeneous distribution of reporting rates was observed throughout the state. A total of 20.3% of municipalities did not meet the recommended reporting target. The municipalities in the Northwest, Jequitinhonha and Vale do Aço macro-regions had the highest reporting rates in the state, while those in the East, East South and West macro-regions had the lowest rates. The number of nursing professionals per inhabitant (regression coefficient= 0.644; p< 0.01) and the percentage of families living in rural areas (regression coefficient= -0.013; p< 0.01) were associated with reporting rates. Conclusion: the presence of clusters of low reporting rates highlights the need to implement integrated strategies adapted to the particularities of each region to enhance event reporting surveillance.